Longitudinal Assessment of T1 Mapping Trends Disease in Pediatric Patients With Heart Transplant - Nicolle M. Ceneri; Ravi Vegulla; Nicholas Mouzakis; Karin Hamann; Devika Richmann; Joshua Kanter; John Berger; Tacy Downing; Yue‐Hin Loke; Steven J. Staffa; David Zurakowski; Russell Cross; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Surveillance for heart transplant rejection by endomyocardial biopsy is invasive and may yield false negatives. T1 and T2 mapping from cardiac magnetic resonance can demonstrate elevations with rejection. We sought to evaluate longitudinal changes in T1 and T2 mapping in pediatric patients with heart transplant. Methods and Results A cohort study was performed of pediatric patients with heart transplant who underwent concurrent endomyocardial biopsy and cardiac magnetic resonance with T1 and T2 mapping from December 2019 to July 2024. Segmental values were measured and subsegmental elevations (ie, hotspots) were identified. Subjects were categorized as either treated rejection or no rejection. Peak and mean T1 and T2 values and number of hotspots at/between each time point for patient dyads were compared between the groups. A total of 21 subjects (7 treated rejection, 14 no rejection) with 68 total encounters met inclusion criteria. Peak and mean T1 values were higher in treated rejection patients during the rejection period and decreased with treatment (peak, 1086 versus 1052; mean, 1028 versus 1021), such that at last follow‐up when their rejection had resolved, there was no significant difference in values when compared with no rejection patients (peak, 1066; mean, 1016). The number of T1 hotspots decreased after rejection treatment (2 versus 1). There were no changes in peak or mean T2 values in the treated rejection group despite treatment, and peak and mean T2 values were similar to patients with no rejection through last follow‐up. Conclusions Elevated T1 values and hotspots observed during cardiac allograft rejection decline in response to treatment. Cardiac magnetic resonance may serve as a noninvasive monitoring tool for the development and resolution of rejection, as well as the effectiveness of rejection therapy.